From automation to databased business models - digitalization and its links to innovation in small and medium-sized enterprises - Jörg Thomä; Thore S. Bischoff (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2022)
In order to provide a better basis for measuring the complex interplay between digital technologies, competences and innovation, the present paper examines the digitalization-innovation link in small and medium-sized enterprises (SMEs). Starting from a review of the fourth edition of the Oslo Manual, a qualitative content analysis of interview data on innovating German SMEs is conducted to derive a category system that covers the multidimensional relationship between digitalization and firm-level innovation. Its empirical application confirms the heterogeneity of innovating SMEs with regard to digital transformation. While some SMEs are slow to find their way into digitalizing their innovation processes, others have started to use new digital technologies for efficiency reasons in the sense of "doing the same with less", while still others are aligning their entire business model with the requirements of digital environments based on the innovation principle of "doing something new". The paper concludes with implications for innovation measurement, managers, policy and research.
Keywords: D22; O31; O32; O33; 330; Digitalization; Digital innovation; Innovation measurement; Qualitative content analysis; SMEs